Epidemiological and genetic analysis of Cetacean Morbillivirus circulating on the Italian coast between 2018 and 2021 - Vargas-Castro, Ignacio; Peletto, Simone; Mattioda, Virginia; Goria, Maria; Serracca, Laura; Varello, Katia; Sánchez-Vizcaíno, José Manuel; Puleio, Roberto; Nocera, Fabio Di; Lucifora, Giuseppe; Acutis, Pierluigi; Casalone, Cristina; et al. (Frontiers in Veterinary Science, 2023)
Cetacean morbillivirus (CeMV) has caused several outbreaks, unusual mortality events, and interepidemic single-lethal disease episodes in the Mediterranean Sea. Since 2012, a new strain with a northeast (NE) Atlantic origin has been circulating among Mediterranean cetaceans, causing numerous deaths. The objective of this study was to determine the prevalence of CeMV in cetaceans stranded in Italy between 2018 and 2021 and characterize the strain of CeMV circulating. Out of the 354 stranded cetaceans along the Italian coastlines, 113 were CeMV-positive. This prevalence (31.9%) is one of the highest reported without an associated outbreak. All marine sectors along the Italian coastlines, except for the northern Adriatic coast, reported a positive molecular diagnosis of CeMV. In one-third of the CeMV-positive cetaceans submitted to a histological evaluation, a chronic form of the infection (detectable viral antigen, the absence of associated lesions, and concomitant coinfections) was suspected. Tissues from 24 animals were used to characterize the strain, obtaining 57 sequences from phosphoprotein, nucleocapsid, and fusion protein genes, which were submitted to GenBank. Our sequences showed the highest identity with NE-Atlantic strain sequences, and in the phylogenetic study, they clustered together with them. Regarding age and species, most of these individuals were adults (17/24, 70.83%) and striped dolphins (19/24, 79.16%). This study improves our understanding on the NE-Atlantic CeMV strain in the Italian waters, supporting the hypothesis of an endemic circulation of the virus in this area; however, additional studies are necessary to deeply comprehend the epidemiology of this strain in the Mediterranean Sea.